Optimization of the Level of Chickpea Sourdough and Baking Powder in Cake Formulation by Response Surface Methodology: Effects on Physicochemical, Sensory and Antioxidant Properties - Hayta, Mehmet; Ertop, Muge Hendek (Japanese Society for Food Science and Technology, 2018)
The chickpea sourdough, also known as "sweet yeast", has not been experimented in chemically leavened bakery products such as cake so far, although it has been used in traditional breads. The aim of this study was to optimize the amounts of chickpea sourdough (A) and baking powder (B) in cake formulation and by examining various quality parameters. An experimental design suggested by Response Surface Methodology, Central Composite Design was used for optimization. The optimization results were validated experimentally. The cake, produced according to the optimized model (OC) was compared with the control cake (CC) in terms of various quality parameters. According to the results, optimum levels of usage were 64.02 g for A and 5.97 g for B. Smaller and more homogeneous pore structures were obtained in OC texture by the use of A according to the image analysis. The cake also acquired slightly sour, sweetish and soft sensory profiles. DPPH radical scavenging activity and physicochemical properties were also improved by the use of the chickpea sourdough.